Influência do método pilates na força e atividade elétrica dos músculos respiratórios de idosas - ensaio clínico controlado randomizado - Fonsêca, Aline Medeiros Cavalcanti da (2012)
The reduction of physiological capacity present in the process of aging causes a marked decline in lung function. The exercise does promote several positive changes in the physical health of people and protect the cardiorespiratory function. The aim of this study was to investigate the effects of a program of Pilates exercices on the strengh and electrical activity of respiratory muscles of elderly. This is a randomized, controlled clinical trial, evaluating 33 elderly aged 65 and 80 (70.88 ± 4.32), healthy, sedentary, without cognitive impairment and able the practice physical activity. The sample was divided into two groups, one experimental group with 16 elderly women who did Pilates exercises and a control group (17) that was not submitted to the exercises, but received educational booklets on aging and health care. The elderly were evaluated initially and after a period of three months, taking into account the Maximal Inspiratory Pressure (MIP) and Maximal Expiratory Pressure (MEP), obtained by Manovacuometry and intensity of EMG activity was measured using the values of Root Mean Square (RMS) for the diaphragm and rectus abdominis muscles, during the course of diaphragmatic breathing and MIP maneuver. Data were analyzed using SPSS version 17.0. For all tests, we used a significance level or p value < 0.05 and confidence interval 95%. RMS in diaphragm and rectus abdominis muscles in both tests increased, but the data were significant for the rectus abdominis during diaphragmatic breathing (p = 0.03) and the diaphragm during the MIP maneuver (p = 0.01). There was no significant variation of the MIP and MEP. Pilates exercises were responsible for increasing the electrical activation of the diaphragm and rectus abdominis muscles in a group of healthy elderly, but had no influence on changes in strength of respiratory muscles